Capital social e governança local no contexto do arranjo produtivo local de móveis do sudoeste do Paraná - Corrêa Neto, Gilcindo de Castro (2018)
The main objective of this work was to analyze the elements of the social capital of the agents and the actions carried out by the local government, in the specific case of the Furniture Cluster of the southwestern region of Paraná. The present research is classified as descriptive of exploratory nature and data are used with qualitative and quantitative approaches. During the exploratory phase the method of documentary analysis and semi-structured interviews was used. The questionnaire was the main instrument of data collection used to obtain information on social capital and local governance. The technique used for data collection was field research, conducted through structured interviews with agents previously selected and executed in the period from October 27, 2017 to December 7, 2017. The research universe involved 19 (nineteen) entrepreneurs of the furniture sector, 05 (five) support agents and 01 (one) agent of local governance. The results of the research point to good levels of social capital and, on the other hand, demonstrate unfavorable indicators regarding the conduction of local governance of the productive arrangement under discussion. Among the elements of social capital, the degree of contribution of the relationship by the associated entrepreneurs was the best evaluated variable. Also, the levels of trust, cooperation, contribution in the relationship of the support agents, quality and usefulness of the information exchanged and contribution in the Cluster as a whole also presented good evaluations. In relation to the social network metrics, it is emphasized that the density was evaluated as median and reciprocity obtained a good result. On the other hand, the variables related to participation in meetings, periodicity in the exchange of information and engagement and commitment of the agents were evaluated with indices considered weak. Regarding the evaluations of the elements of local governance, all showed poor or poor levels. In the discussion of the binomial social capital and local governance, one can perceive a coherence between the unfavorable evaluations, which appear to be directly related to the lack or absence of coordination of the Cluster through the need for a more active local governance. The social capital observed in the group of support agents, together with the elements found positive in the other agents, can provide a significant increase in the overall network context. In the case of local governance, it will be necessary to work together among the agents to develop leaders in the group, in order to arouse the interest of capable and committed people to assume the coordination of the arrangement. In addition, the most important limitation observed during the study was the current absence of local governance, which is in a process of reconstruction. In this sense, it is recommended as future work, the realization of new studies in the productive arrangement, aiming to observe if the reorganization of the governance is contributing with the results of the evaluation of the binomial social capital and governance in the context of this Cluster.